(untitled) (Research, Society and Development, 2025)
Brazil is one of the countries that performs the most plastic surgeries in the world. Currently, mastopexy associated with breast implants is one of the most frequently performed procedures in Brazil. The article aims to analyze the techniques and risks of mastopexy with breast implants. The narrative bibliographic review methodology was used to prepare the study. Regarding the surgical technique, mastopexy can be performed in different ways and each one has its own indication. The periareolar technique is used in patients who have a small degree of ptosis and smaller size. It is the least invasive technique, with the smallest scar. Mastopexy with a vertical scar presents a greater degree of invasion in relation to the periareolar technique. It is indicated for breasts that have moderate ptosis and intermediate size. The technique with an inverted “T” scar is the most widely used model. It is the most invasive technique, being indicated for severe and serious ptosis, with larger breasts, greater amount of skin and fatty tissue. Regarding the prosthesis, silicone can be implanted subglandularly and submuscularly, with submuscular being the most commonly used for patients who have undergone mastopexy. Therefore, an individualized analysis of each patient is essential to choose the best option, and the plastic surgeon must take into account scientific evidence and the patient’s wishes.